Gender-based differences in harm reduction practices among people who use drugs in Rhode island: a latent class analysis - Leah C. Shaw; Anusha Kumar; Carolyn J. Park; Yu Li; Catherine A. Lenox; Alexandra B. Collins; Susan G. Sherman; Brandon D. L. Marshall; Alexandria Macmadu (Harm Reduction Journal)
Abstract Background Previous research has documented differing drug use patterns and risk behaviors by gender identity and sex at birth, although variations in harm reduction practices by these characteristics have not yet been fully assessed. Methods We utilized data from the Rhode Island Prescription and Illicit Drug Study (RAPIDS), which enrolled adults who used drugs from 2020 to 2023. Participants were analyzed based on gender identity: men, women, and other (including those identifying as non-binary or something else). Participants reported which harm reduction practices (e.g., use fentanyl test strips, keep naloxone nearby) they typically engaged in to avoid accidental overdose. Latent class analysis (LCA) was used to identify subgroups of harm reduction practice typologies, and a correlation matrix was generated to understand dyads of typical self-reported harm reduction practices. Results Among 503 eligible participants, 64% were men, 34% were women, and 2% were non-binary or something else (n = 9). Harm reduction practices were comparable between men and women, although men were less likely to keep naloxone nearby (p = 0.02). LCA identified three subgroups of harm reduction practice typologies (no/low, moderate, and high utilization). Group membership in latent classes did not vary by gender identity. However, those belonging to the no/low utilization subgroup were significantly more likely to have ever been incarcerated (p = 0.03) and to be single (p < 0.01). Those belonging to the high utilization group were significantly more likely to have ever witnessed an overdose, performed rescue breathing, and administered naloxone (all p < 0.001). Correlations showed several pairwise relationships, with ‘use fentanyl test strips’ and ‘keeping naloxone nearby’ being positively and significantly correlated (r = 0.33, p < 0.05). Conclusions We found that harm reduction practices and group membership in latent classes were largely comparable between men and women; however, men who use drugs are significantly less likely to keep naloxone nearby. Gender-attentive strategies to increase naloxone carriage and usage among men and enhanced outreach to persons characterized by no or low harm reduction practice utilization, including people who are single and those with a history of incarceration, may be warranted to mitigate overdose risk.